2003
DOI: 10.1159/000072424
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Identification of the Na<sup>+</sup>/H<sup>+</sup> Exchange Isoforms NHE1 and NHE3 in Isolated Bovine Articular Chondrocytes

Abstract: Cartilage matrix turnover is sensitive to changes in intracellular pH (pHi) and previous studies have shown that articular chondrocytes regulate pHi predominantly using an amiloride-sensitive Na+ / H+ exchanger (NHE) with hallmark properties of the housekeeper isoform NHE1. Immunoblotting studies have, however, demonstrated that bovine chondrocytes express both the NHE1 and NHE3 isoforms of Na+ / H+ exchange. In the present study the effect of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…The NHE response to growth factors and cytokines commonly reflects the activation of this protein by direct phosphorylation, Ca 2+ -calmodulin complex binding or altered interactions with regulatory proteins, and the rapidity of our response suggests similar events are occurring here. In chondrocytes, growth factors upregulate the activity of the NHE1 isoform, as well as inducing expression of NHE3 [13]. Here, however, the observation that NHE-1 specific HOE694, amiloride and removal of Na + ions all inhibited acid extrusion to the same degree indicates that the enhanced NHE activity is solely mediated by NHE1.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The NHE response to growth factors and cytokines commonly reflects the activation of this protein by direct phosphorylation, Ca 2+ -calmodulin complex binding or altered interactions with regulatory proteins, and the rapidity of our response suggests similar events are occurring here. In chondrocytes, growth factors upregulate the activity of the NHE1 isoform, as well as inducing expression of NHE3 [13]. Here, however, the observation that NHE-1 specific HOE694, amiloride and removal of Na + ions all inhibited acid extrusion to the same degree indicates that the enhanced NHE activity is solely mediated by NHE1.…”
Section: Discussionmentioning
confidence: 53%
“…In contrast, ADAMTS4 activity is controlled largely by posttranscriptional activation involving furin and MT4-MMP. [13][14][15][16]. In mammalian chondrocytes, HCO 3 --dependent membrane transport processes do not operate to a great extent, probably because the expression and activity of carbonic anhydrase is low [17].…”
mentioning
confidence: 99%
“…Confluent cells were incubated with each inhibitor at different concentrations until the dome appeared in control cells. S3226 was kindly provided by Dr. Robert J. Wilkins (33). Oncostatin M was purchased from PeproTech EC Ltd (London, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Fish were the first vertebrates; thus these exchangers may be important for bone formation or resorption. Preliminary studies in osteoclasts showed a role for Na ϩ /H ϩ exchange in H ϩ extrusion linked to bone resorption (92,132) and in pH regulation of chondrocytes (141,145). Fish were the first species to have a cardiovascular system responsible for respiratory exchange (unlike invertebrate hearts that just circulated nutrients), and although some gastropods have gills, fish species were the first to have evolved advanced gills for respiratory exchange (which evolved into lungs in amphibians and more complex species).…”
Section: Utility Of Model Organisms In the Study Of Nhesmentioning
confidence: 99%